Adverse life experiences and risk of unintended pregnancy in adolescence and early adulthood: Implications for toxic stress and reproductive health - Kelli Stidham Hall; Jennifer L. Beauregard; Shelby T. Rentmeester; Melvin Livingston; Kathleen Mullan Harris (Elsevier, 2019)
Objective: We examined the effects of adverse life experiences (ALEs) on rates of unintended first pregnancy, including differential effects by race/ethnicity and socioeconomic status, among women in a national longitudinal cohort study. Methods: We drew upon 15-years of data from 8810 adolescent and young adult females in the National Longitudinal Study of Adolescent to Adult Health. Using 40 different ALEs reported across childhood and adolescence, we created an additive ALE index, whereby higher scores indicated greater ALE exposure. We employed Cox proportional hazard models, including models stratified by racial/ethnic and socioeconomic groups, to estimate the effects of ALEs on time to first unintended pregnancy, controlling for time-varying sociodemographic, health and reproductive covariates. Results: Among all women, a 1-standard deviation increase in ALE scores was associated with an increased rate of unintended first pregnancy (adjusted Hazard Ratio 1.11, 95% Confidence Interval=1.04-1.17). In stratified models, associations between ALE scores and risk of unintended pregnancy varied across racial/ethnic, socioeconomic, and age groups and according to various elevated ALE thresholds. For example, the 1-standard deviation increase in ALE score indicator increased the unintended pregnancy risk for African-American (aHR=1.12, CI=1.01-1.25), Asian (aHR 1.69, CI=1.26-2.26), and White women (aHR=1.12, CI=1.03-1.22), women in the lowest ($0-$19,999; aHR=1.21, CI = 1.03-1.23) and highest (>$75,000; aHR=1.36, CI=1.12-1.66) income categories, and women aged 20-24 (aHR=1.13, CI=1.04-1.24) and >24 years (aHR 1.25, CI=1.06-1.47), but not among the other sociodemographic groups. Conclusion: ALEs increased the risk of unintended first pregnancy overall, and different levels of exposure impacting the risk of pregnancy differently for different sub-groups of women. Our ongoing research is further investigating the role of stress-associated adversity in shaping reproductive health outcomes and disparities in the United States.